Long-Term Comparative Effectiveness of Transcatheter Aortic Valve Replacement (TAVR) Versus Surgical Aortic Valve Replacement (SAVR) in High-Risk Aortic Stenosis Patients: A Meta-Analysis - Senthanu, I Gede Andrika Indrayoga; Dewa Ayu Agung Maya Gayatri (Open Access Indonesian Journal of Medical Reviews, 2024)
Transcatheter aortic valve replacement (TAVR) has become an alternative to surgical aortic valve replacement (SAVR) for high-risk patients with severe aortic stenosis (AS). This meta-analysis aims to compare the long-term outcomes of TAVR and SAVR in this population. A systematic search of PubMed, Embase, and the Cochrane Library was conducted up to December 2023. Randomized controlled trials (RCTs) and observational studies comparing TAVR and SAVR with a minimum follow-up of one year were included. The primary outcome was all-cause mortality. Secondary outcomes included cardiovascular mortality, stroke, myocardial infarction (MI), and rehospitalization. Twenty-three studies involving 15,482 patients (TAVR=7,785, SAVR=7,697) were included. The mean follow-up period was 3.2 years (range 1-5 years). There was no significant difference in all-cause mortality between TAVR and SAVR (Hazard Ratio [HR] 1.02, 95% CI 0.95-1.09, p=0.63). Similarly, there were no differences in cardiovascular mortality (HR 1.05, 95% CI 0.96-1.15, p=0.28), stroke (HR 0.98, 95% CI 0.87-1.10, p=0.75), or MI (HR 0.94, 95% CI 0.82-1.08, p=0.39). However, TAVR was associated with a lower rate of rehospitalization (HR 0.85, 95% CI 0.78-0.93, p=0.001). TAVR is a viable alternative to SAVR in high-risk patients with AS, demonstrating comparable long-term survival and safety outcomes. The reduced rehospitalization rate associated with TAVR may be an important consideration for these patients.